Provider Adherence to the 2020 US Multi-Society Task Force Guidelines for Surveillance After Colonoscopy With Polypectomy - Benjamin E. Cassell; Katherine Scholand; Wyatt Tarter; Camille J. Hochheimer; Colleen Long; Gregory L. Austin (Gastro Hep Advances)
Background and Aims: The 2020 United States Multi-Society Task Force on Colorectal Cancer guidelines for surveillance after colonoscopy with polypectomy introduced significant changes in surveillance intervals. We sought to identify rates of adherence to these new guidelines at an academic medical center. Methods: Average-risk screening colonoscopies where 1 to 4 polyps <10 mm were removed between January 1, 2020, and June 30, 2021 were included. To determine predictors of nonadherence, a multivariable logistic regression analysis was conducted and included patient and procedure-related variables. Bayesian changepoint analysis was applied to identify timing of change in adherence. Multinomial logistic regression was used to identify predictors of variability within the guidelines. Results: One thousand twenty-six procedures were analyzed. Adherence to the guidelines was 85%. In procedures with 1 to 2 polyps, increasing size (odds ratio [OR] 0.84 per mm; 95% confidence interval [CI]: 0.75–0.93) and a mixture of tubular adenomas (TA) and hyperplastic polyps (OR 0.35; 95% CI: 0.21–0.59) were associated with nonadherence. Among procedures with 1 to 2 TAs, age (OR 0.86 per 5-year increase; 95% CI: 0.75–0.99), increasing size (OR 0.86 per mm; 95% CI: 0.75–0.99) and polyp number (OR 0.54; 95% CI: 0.33–0.90) were associated with nonadherence. Changepoint analysis identified a potential changepoint on September 2, 2020 (95% credible interval April 2, 2020–February 22, 2020). Larger TAs were less likely to receive a 10-year recommendation (OR 0.61, 95% CI 0.5–0.75). Conclusion: Adherence rates to the 2020 surveillance guidelines were high with a potential changepoint identified on 2/9/20. Deviation from guidelines was associated with patient and procedure related variables.